1994
DOI: 10.1002/hrm.3930330105
|View full text |Cite
|
Sign up to set email alerts
|

Human resource strategies and contingent workers: The case of safety and health in the petrochemical industry

Abstract: One of the most important economic developments in recent years is the growth in the number of temporary and contract employees. Little is known, however, about the implications these contingent employees have for human resource practices. This paper presents the results of a study of one group of contingent workers, contract workers in the petrochemical industry. The primary concern of this study is the consequences contract workers have for safety, a hotly debated and politically charged issue in an industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 7 publications
4
92
1
4
Order By: Relevance
“…Within this group of workers we find people on a variety of different contracts, including those who work on a temporary basis, but are directlyemployed, and also those who are engaged on a short-term basis through an employment agency. When first considering temporary workers, it is found that, as well as experiencing poorer working conditions based on factors such as pay and job stability (Deutsch, 2005;Eib et al, 2014), resulting in lower levels of job satisfaction and organisational commitment (Author et al, 2014;Vujičić et al, 2014), this group have also been found to receive lower levels of training, notably in induction (Kochan et al, 1994;Selcraig, 1992). Managerial models such as Atkinson's (1985) core-periphery model divide workers on contractual status, suggesting that these temporary workers should be engaged on a transactional rather than relational basis (Williamson and Ouchi 1983;Williamson 1985Williamson , 1996 and be utilised to create numerical flexibility.…”
Section: Divisions Between Core and Temporary Workersmentioning
confidence: 99%
“…Within this group of workers we find people on a variety of different contracts, including those who work on a temporary basis, but are directlyemployed, and also those who are engaged on a short-term basis through an employment agency. When first considering temporary workers, it is found that, as well as experiencing poorer working conditions based on factors such as pay and job stability (Deutsch, 2005;Eib et al, 2014), resulting in lower levels of job satisfaction and organisational commitment (Author et al, 2014;Vujičić et al, 2014), this group have also been found to receive lower levels of training, notably in induction (Kochan et al, 1994;Selcraig, 1992). Managerial models such as Atkinson's (1985) core-periphery model divide workers on contractual status, suggesting that these temporary workers should be engaged on a transactional rather than relational basis (Williamson and Ouchi 1983;Williamson 1985Williamson , 1996 and be utilised to create numerical flexibility.…”
Section: Divisions Between Core and Temporary Workersmentioning
confidence: 99%
“…Additionally, these workers are not typically given company benefits, which further widen the gap in pay. In a study of the petrochemical industry, contract workers received 60 % less pay for performing the same work as permanent employees (Kochan, Smith, Wells & Rebitzer, 1994).…”
Section: Pay For Performancementioning
confidence: 99%
“…En effet, les gestionnaires ne o 1 peuvent pas toujours justifier un investissement dans des programmes de formation ou de gestion des compétences lorsque la durée du lien d'emploi est courte ou imprévisible (Kochan et al 1994 ;Schellenberg 1997), et les travailleurs atypiques ne se voient pas toujours offrir les mêmes opportunités de carrière que leurs collègues en emploi traditionnel (Rotchford et Roberts 1982).…”
Section: Les Défis Posés Par Le Travail Atypiqueunclassified
“…Sur le plan professionnel, les compétences de certains travailleurs au statut atypique risquent de devenir rapidement désuètes car les employeurs hésitent souvent à investir dans la formation d'une main-d'oeuvre non permanente (Kochan et al 1994 ;Schellenberg 1997). Le risque est d'autant plus grand pour les travailleurs dont la relation avec l'employeur est de courte durée, comme les travailleurs temporaires, contractuels ou d'agence.…”
Section: Un Choix Individuel éClairéunclassified
See 1 more Smart Citation